1995
DOI: 10.1111/j.1445-2197.1995.tb01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gastrografin Study in the Assessment of Anastomotic Leaks From Cervical Oesophagogastric Anastomosis

Abstract: Gastric pull‐up with cervical oesophagogastric anastomosis is a common procedure after oesophageal resection. Contrast studies are used by many surgeons for detection of anastomotic leaks but may be unnecessary. A prospective study was undertaken to compare gastrografin study and test feeding using water for detection of cervical anastomotic leaks. In 25 patients. gastrografin study showed three leaks, two of which were clinically silent and patients did not have any problems. One patient had aspiration of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Three false or pseudo-leaks were suggested on contrast swallow, as has been described previously [24,32,33]. Well-performed contrast studies and detailed knowledge of the type of surgical anastomosis used is imperative if contrast swallow examinations are to be correctly interpreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three false or pseudo-leaks were suggested on contrast swallow, as has been described previously [24,32,33]. Well-performed contrast studies and detailed knowledge of the type of surgical anastomosis used is imperative if contrast swallow examinations are to be correctly interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this is of poor sensitivity and specificity, failing to identify clinically significant anastomotic leaks or demonstrating pseudo-leaks (contrast cascade due to endto-side anastomosis rather than leak) [10,21]. As a result, some suggest that the routine use of contrast swallow be discontinued [22][23][24][25]. Lamb et al in a study of 66 patients showed routine contrast swallow to have a sensitivity of 66.6% and concluded that there is no role for routine contrast swallow after total gastrectomy.…”
mentioning
confidence: 99%
“…219 All patients underwent a contrast (Gastrografin) study on the day 5 postoperatively, followed by 'test feeding' with drinking water in the surgical ward. The drain site dressings were removed and the drain site…”
Section: Gollub and Bainsmentioning
confidence: 99%
“…Evans et al, Surgery: pancreatic surgery Definition: as below 1997, 248 UK (n = 63) Clinical features: not described Aim: a largely prospective study to analyse the medium-term outcome Investigations: the presence of a pancreatic fistula was defined by the of surgery for chronic pancreatitis, production of > 50 ml/day abdominal fluid with an amylase content of with particular emphasis on the > 1000 unit/l (normal value < 300 unit/l) quality of life for patients based on the mortality and morbidity rates associated with surgery, relief of symptoms, analgesic use, employment and long-term sequelae of pancreatic surgery 293 and orthotopic bladder substitution Germany via the ileal neobladder Clinical features: not described, but the authors do refer to insufficiency of the ileal anastomosis Aim: to report on the morbidity and complications of a series of 306 men Investigations: a variety of examinations were conducted over the who received an ileal neobladder and follow-up period (3-month intervals in years 1 and 2, 6-month intervals in in whom complete follow-up was years 3 and 4, annually thereafter 219 India Aim: a prospective study comparing Clinical features: leak at neck site Gastrografin study with test feeding (done in the surgical ward using Investigations: routine imaging, regardless of clinical signs. All patients drinking water) in a series of underwent Gastrografin study on day 5 postoperatively, followed by 'test 25 consecutive patients with cervical feeding' with drinking water (more description is given on p. 68) oesophagogastric anastomosis.The issues to be answered were: (1) are any anastomotic leaks missed by using 'test feeding' instead of Gastrografin study; and (2) Investigations: soluble contrast enema was used to confirm clinical altered haemostatic balance in the suspicion.…”
Section: Medline and Healthstarmentioning
confidence: 99%
“…apparent leaks represented only a proportion of the total who had radiological anastomotic leaks [3,[10][11][12][13] .…”
mentioning
confidence: 99%